trans-3-Chloroacrylic Acid Dehalogenase from Pseudomonas pavonaceae 170 Shares Structural and Mechanistic Similarities with 4-Oxalocrotonate Tautomerase - Poelarends, Gerrit J. (American Society for Microbiology, 2001)
The genes (caaD1 and caaD2) encoding the trans-3-chloroacrylic acid dehalogenase (CaaD) of the 1,3-dichloropropene-utilizing bacterium Pseudomonas pavonaceae 170 were cloned and heterologously expressed in Escherichia coli and Pseudomonas sp. strain GJ1. CaaD is a protein of 50 kDa that is composed of α-subunits of 75 amino acid residues and β-subunits of 70 residues. It catalyzes the hydrolytic cleavage of the β-vinylic carbon-chlorine bond in trans-3-chloroacrylic acid with a turnover number of 6.4 s(−1). On the basis of sequence similarity, oligomeric structure, and subunit size, CaaD appears to be related to 4-oxalocrotonate tautomerase (4-OT). This tautomerase consists of six identical subunits of 62 amino acid residues and catalyzes the isomerization of 2-oxo-4-hexene-1,6-dioate, via hydroxymuconate, to yield 2-oxo-3-hexene-1,6-dioate. In view of the oligomeric architecture of 4-OT, a trimer of homodimers, CaaD is postulated to be a hexameric protein that functions as a trimer of αβ-dimers. The sequence conservation between CaaD and 4-OT and site-directed mutagenesis experiments suggested that Pro-1 of the β-subunit and Arg-11 of the α-subunit are active-site residues in CaaD. Pro-1 could act as the proton acceptor/donor, and Arg-11 is probably involved in carboxylate binding. Based on these findings, a novel dehalogenation mechanism is proposed for the CaaD-catalyzed reaction which does not involve the formation of a covalent enzyme-substrate intermediate.